The Role of Rumah Qur'an in Improving the Quality of Akhlakul Karimah in Children at Rumah Qur'an Rumish Klaten - Putri Aqilah Salsabila; Mutohharun Jinan (Electronic Journal of Education, Social Economics and Technology, 2025)
An essential role in improving the quality of individual and community life is education. One of the non-formal educational institutions that contribute to moral and spiritual development is Rumah Qur'an. The purpose of this study is to analyze the role of Rumah Qur'an in enhancing the quality of Akhlakul Karimah in children at Rumah Qur'an Rumish Klaten, using a qualitative approach and case study method. Data were obtained through interviews, participant observation, and document studies. This research reveals that Rumah Qur'an Rumish Klaten plays a role in character building through Qur'an learning, moral education, and the habituation of Islamic values in daily life. Teaching and learning activities take place four times a week. Additionally, the Akhlakul Karimah development methods are applied through role modeling, habituation, as well as providing advice and guidance to students. Although Rumah Qur’an has a positive impact, this study also found several challenges in implementing Akhlakul Karimah development, such as the uncontrolled use of mobile phones at home. Therefore, a more comprehensive strategy is needed, including collaboration between institutions, families, and the community. Thus, Rumah Qur'an Rumish Klaten plays a significant role in improving the quality of Akhlakul Karimah in children through a systematic Qur'an-based education. However, optimizing development methods is necessary to achieve more effective and sustainable results.